Odpowiedź:
a) x ( 2x² + 3x - 5 ) - [tex]\frac{3x^{2} (2x-1)+12}{3}[/tex] = 2[tex]x^{3}[/tex] + 3[tex]x^{2}[/tex] - 5x - [tex]x^{2}[/tex](2x - 1) + 4
= 2[tex]x^{3}[/tex] + 3[tex]x^{2}[/tex] - 5x - 2[tex]x^{3}[/tex] + [tex]x^{2}[/tex] + 4 = 4[tex]x^{2}[/tex] - 5x
b) [tex]\frac{21a-7(2b+c)}{-7}[/tex] - 5(-2a + b - 3c) = -3a + 1(2b + c) + 10a - 5b + 15c =
= -3a + 2b + c + 10a - 5b + 15c = 7a - 3b + 16c
c) -3x (-x² + 2x - 4) + [tex]\frac{18x(5-x)-6x^{3} }{-6}[/tex] = 3[tex]x^{3}[/tex] - 6[tex]x^{2}[/tex] + 12x - 3(5 - x) + [tex]x^{3}[/tex] =
= 3[tex]x^{3}[/tex] - 6[tex]x^{2}[/tex] + 12x - 15 + 3x + [tex]x^{3}[/tex] = 4[tex]x^{3}[/tex] - 6[tex]x^{2}[/tex] + 15x - 15